Retrospective Analysis of Pediatric Hepatoblastoma With Tumor Rupture: Experience From a Single Center - Zhang, Yu-Tong; Zhao, Yu-Fei; Yang, Dian-Fei; Chang, Jian (Frontiers in Pediatrics, 2022)
Purpose Hepatoblastoma (HB) tumor rupture is currently considered as a high-risk factor in some risk stratification systems. This study aimed to investigate the value of HB tumor rupture in predicting the poor prognosis. Methods The clinical data from children with high-risk HB or HB tumor rupture at our institution from October 2008 to 2017 were retrospectively reviewed and analyzed. Results Together, 34 children with high-risk HB or HB tumor rupture were retrospected, including 25 in the high-risk group and nine in tumor rupture group. The 3-year overall survival (OS) rate in tumor rupture group was significantly higher than that of the high-risk group (100 vs. 64%, p = 0.0427). In tumor rupture group, seven (77.8%) of nine patients had a hemoglobin level ≤ 8 g/L and 3 of them (33.3%) had ≤ 6 g/L at the time of diagnosis. Peritoneal perfusion with interleukin-2 was implemented for each patient. At the end of the treatment, seven (77.8%) of nine patients achieved complete response (CR). No patient died at the last follow-up. Conclusions HB tumor rupture might not be predictive of poor prognosis with the risk of peritoneal dissemination/relapse, in which peritoneal perfusion with interleukin-2 could play a role.